Addiction and change: how addictions develop and addicted people recover - DiClemente, Carlo C. (The Guilford substance abuse series, 2003)
1. Models of addiction and change -- 2. The process of human intentional behavior change -- 3. The well maintained addiction : an ending and a beginning -- 4. Exploring precontemplation, contemplation, and preparation stages of becoming addicted -- 5. Repeated and regular use : moving from preparation to action on the road to addiction -- 6. Precontemplation for recovery : cultivating seeds for change -- 7. The decision to change : moving from the contemplation to the preparation stage of recovery -- 8. Preparing for action : creating a plan -- 9. Taking action to change an addiction -- 10. The long haul : well-maintained recovery -- 11. Prevention : interfering with the process of becoming addicted -- 12. Designing interventions for recovery -- 13. Research on addiction and change